Track II diplomacy meets action research: fostering collaborative foreign policy between Türkiye and the EU in North Africa - Pınar Akpınar (22997476) (2025)
This article explores the integration of Participatory Action Research (PAR) into foreign policy design, positioning it as a transformative tool to operationalise Track II diplomacy and foster inclusive, stakeholder-driven approaches. Focusing on EU – Türkiye cooperation in North Africa – particularly in Morocco, Algeria, and Egypt – the study applies PAR methodologies such as search conferences and clinical interviews with triangulation of other methods such as expert surveys to identify stakeholder-driven policy priorities. These include educational mobility, public infrastructure, health, renewable energy, and food security. While designed to engage both Track I and Track II actors, the process revealed the challenges of limited official participation, especially from North African governments, due to civic space restrictions and political sensitivities. Nonetheless, the findings demonstrate that PAR can build trust, surface actionable cooperation models, and complement conventional diplomacy. By moving beyond traditional security-focused Track II initiatives, the article contributes to rethinking foreign policy as a collaborative and participatory process. Ultimately, PAR is presented as a replicable, action-oriented model that complements conventional diplomacy and contributes to ongoing debates on democratising international relations through more adaptive and inclusive practices. Other Information Published in: Third World Quarterly License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/01436597.2025.2556319